Enhancement of energy harvesting capability using PVDF/GFRP-laminated films. (October 2019) - Wu, Guihua; Li, Alamusi; Wu, Liangke; Hu, Ning; Yao, Jianyao; Zhang, Jianyu; Yuan, Weifeng; Ning, Huiming; Liu, Yaolu; Atobe, Satoshi; Fukunaga, Hisao
PVDF (poly(vinylidene fluoride)) is a promising piezoelectric polymer which can be applied in sensor or energy harvesting fields. To improve the energy harvesting capability of the PVDF film, we proposed a laminated piezoelectric element consisting of two PVDF films sandwiching a GFRP (glass fiber-reinforced plastic) laminate, named as PVDF/GF/PVDF. Its energy harvesting capability and open circuit voltage were experimentally investigated. Compared with PVDF monolayer and bilayer piezoelectric elements, this newly designed PVDF/GF/PVDF possesses remarkably increased energy harvesting capabilities in both AC and DC circuits. The mechanisms for this phenomenon were explored experimentally, theoretically and numerically in detail. Compared with the PVDF monolayer element, the increases of harvested power in the PVDF bilayer element and the PVDF/GF/PVDF are mainly due to their larger PVDF net volume. Compared with the PVDF bilayer element, the reason for the increase of the energy harvesting capability in the PVDF/GF/PVDF is its higher piezoelectric stress constant caused by the insertion of stiffer GFRP laminate.